BMSC-Derived Exosomes Inhibit Dexamethasone-Induced Muscle Atrophy via the miR-486-5p/FoxO1 Axis - Li, Ziyi; Liu, Chang; Li, Shilun; Li, Ting; Li, Yukun; Wang, Na; Bao, Xiaoxue; Xue, Peng; Liu, Sijing (Frontiers in Endocrinology, 2021)
Sarcopenia, characterized by reduced muscle function as well as muscle mass, has been a public health problem with increasing prevalence. It might result from aging, injury, hormone imbalance and other catabolic conditions. Recently, exosomes were considered to regulate muscle regeneration and protein synthesis. In order to confirm the effect of BMSC-derived exosomes (BMSC-Exos) on muscle, Dexamethasone-induced atrophy was built both in vitro and in vivo. In the present research, BMSC-Exos attenuated the decrease of myotube diameter induced by dexamethasone, indicating that BMSC-Exos played a protective role in skeletal muscle atrophy. Further mechanism analysis exhibited that the content of miR-486-5p in C2C12 cells was up-regulated after treated with BMSC-derived exosomes. Meanwhile, BMSC-derived exosomes markedly downregulated the nuclear translocation of FoxO1, which plays an important role in muscle differentiation and atrophy. Importantly, the miR-486-5p inhibitor reversed the decreased expression of FoxO1 induced by BMSC-Exos. In animal experiments, BMSC-Exos inhibited dexamethasone-induced muscle atrophy, and miR-486-5p inhibitor reversed the protective effect of BMSC-Exos. These results indicating that BMSC-derived exosomes inhibit dexamethasone-induced muscle atrophy via miR486-5p/Foxo1 Axis.